Vaccination situation in children of childhood education against Human Rotavirus - Wesp, Luiza Helena dos Santos (2018)
The objective of this study was to analyze the vaccination status of the Human Rotavirus Oral Vaccine in children in early childhood education. The epidemiological, descriptive, retrospective and quantitative approach method was carried out based on information collected on 1 434 copies of vaccination cards of children enrolled in Natal / RN Municipalities for Early Childhood Education. Data were collected from March and December 2015 through the check list. The results show that 78,4% of the analyzed cards were classified as complete vaccination schedule when they had two doses of the vaccine and 11,9% had an incomplete vaccination schedule when they had only one dose and another 9,7% classified as not vaccinated when not registered this vaccine. It was concluded that there was an increase in the number of doses administered in the last years. However, a larger number of unimmunized children in the larger age group were observed